Financial Modelling of Smallholder Seedling Production - Harrison, Steve; Gregorio, Nestor; Wilson, Wendy (Annals of Tropical Research, 2010)
A financial model of smallholder forestry seedling nursery on Leyte Island has been developed as a contribution to the ACIAR project ASEM/2006/091 – Enhancing tree seedling supply via economic and policy changes in the Philippines nursery sector. Two versions of this model have been developed – one for a best management practice nursery and one for a representative smallholder nursery. This paper describes the data collection, and model development and implementation. Some implications are drawn for policy development concerning adoption of best management practice in smallholder nurseries. Possibilities for further development and application of the seedling nursery model are discussed.